2021
DOI: 10.1155/2021/5561569
|View full text |Cite
|
Sign up to set email alerts
|

LC-MS/MS-Based Quantitative Proteomics Analysis of Different Stages of Non-Small-Cell Lung Cancer

Abstract: Lung cancer has a higher incidence rate and mortality rate than all other cancers. Early diagnosis and treatment of lung cancer remain a major challenge, and the 5-year survival rate of its patients is only 15%. Basic and clinical research, especially the discovery of biomarkers, is crucial for improving the diagnosis and treatment of lung cancer patients. To identify novel biomarkers for lung cancer, we used the iTRAQ8-plex labeling technology combined with liquid chromatography-tandem mass spectrometry (LC-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Schulze et al have revealed that the MYC target V2 scores are associated with tumor aggressiveness and survival outcomes in ER-positive primary tumors, as well as in metastatic breast cancer [ 22 ]. Zhou et al found that the levels of spermatogenesis-associated protein increased significantly in the serum of patients with lung cancer compared with those in healthy controls [ 23 ]. The unfolded protein response is a prosurvival mechanism triggered by accumulation of unfolded or misfolded proteins in the endoplasmic reticulum, and unfolded protein response signalling plays important roles in cancer progression [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Schulze et al have revealed that the MYC target V2 scores are associated with tumor aggressiveness and survival outcomes in ER-positive primary tumors, as well as in metastatic breast cancer [ 22 ]. Zhou et al found that the levels of spermatogenesis-associated protein increased significantly in the serum of patients with lung cancer compared with those in healthy controls [ 23 ]. The unfolded protein response is a prosurvival mechanism triggered by accumulation of unfolded or misfolded proteins in the endoplasmic reticulum, and unfolded protein response signalling plays important roles in cancer progression [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic analysis is a great experimental tool for studying protein changes in cells, tissues, or organisms [ 17 ]. Recently, proteomic analysis has been widely used to enable the discovery of potential biomarkers and identification of tumor-related protein expression [ 18 , 19 , 20 ]. Because comparative phosphoproteome analysis can comprehensively quantify altered protein phosphorylation, it is effective to evaluate the intracellular effect of PDK4 as a kinase.…”
Section: Introductionmentioning
confidence: 99%
“…16 Proteomic approaches could be very helpful to identify resistance biomarkers representing the differences between sensitive and resistant cancer cells. 17 Comparative proteomics has successfully performed to identify many key target proteins involved in drug resistance, and several of these proteins have been verified as biomarkers in clinical cancer therapy. 18 Resistance biomarkers still have unmet clinical needs in both diagnosis and prognosis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Proteome is dynamically changing in response to different environments, especially drug treatment . Proteomic approaches could be very helpful to identify resistance biomarkers representing the differences between sensitive and resistant cancer cells . Comparative proteomics has successfully performed to identify many key target proteins involved in drug resistance, and several of these proteins have been verified as biomarkers in clinical cancer therapy .…”
Section: Introductionmentioning
confidence: 99%